FETOMATERNAL OUTCOME IN PREGNANCY WITH GESTATIONAL THROMBOCYTOPENIA - Dr. Aishwarya Meshram; Dr. Azmat Jahan Mantoo; Prof. Dr. Cimona Lyn Saldanha; Dr Umer Hamid (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
BACKGROUND : Thrombocytopenia is second most common hematological abnormality during pregnancy, and is found to complicate 7% to 8% of pregnancy in India. Thrombocytopenia in pregnancy may be an isolated findings or it may be associated with systemic disorders like severe preeclampsia , HELLP syndrome(hemolysis, elevated liver enzymes, low platelets), or AFLP(acute fatty liver of pregnancy). OBJECTIVE : To study the cases of thrombocytopenia during pregnancy and its effect on feto-maternal outcome. MATERIAL AND METHODS: A prospective observational study was carried out in tertiary hospital, 422 pregnant women who attended the antenatal clinic regularly were enrolled ( >30 weeks of gestation). Out of 422 pregnant women, n=211 were women with normal platelet count were taken as control group and those with low count (<150×109/L) ,n= 211 were included in the study group. RESULTS: the mean age of study group was 28.65±2.67 years and in control group was28.87±2.61 years.maternal and perinatal complications like intra op oozing(21.32%), PIH(22.75%), need for transfusion (22%,)hematoma formation(7%), neonatal jaundice (17.06%),neonatal thrombocytopenia(17.53%), birth asphyxia(9.04%),NICU admission(17.53%), need for resuscitation (30.33%),low apgar[<7](32.23%) etc. were more in patients with thrombocytopenia as compared to their age and parity matched controls. CONCLUSION: Study results showed , pregnancies with gestational thrombocytopenia were at higher risk of low Apgar scores, higher rate of admission to the NICU, intracranial hemorrhage , neonatal death or adverse maternal outco×me as compared to the control group.